Dumbo (Usa: Disney Press, 2017)
Dumbo was a very cute and sweet baby elephant. Little cute Dumbo elephant is an all-time favourite of kids.Dumbo was a young circus elephant who was born with comically large ears. He was able to fly because of his large ears.
Text in English
Keywords: Story Books